The estimation of efficiency of insect traps of various construction for phytosanitary monitoring - O. Yu. Kremneva; V. T. Sadkovsky; Yu. G. Sokolov; V. Ya. Ismailov; R. Yu. Danilov (Зерновое хозяйство России, 2019)
Timely and accurate phytosanitary monitoring is of great importance to organize plant protection from pests. Recently, in order to attract and trap (destroy) insects, the use of super bright light emitted diodes (LEDs) has attracted great interest. In this connection, the purpose of our research was to manufacture trap designs based on super bright LEDs for phytosanitary monitoring and to evaluate their efficiency. We have developed and manufactured three models of a conical trap, differing in the way of collecting insects. The first trap (KLP-1) used a cartridge with the entomological glue “Polifiks”. The second trap (KL-2) accumulated insects in a transparent elastic collector of the lower part of the cylinder. The third trap (AKL-2) used the cylinder in the upper part equipped with a low-power aspirator as an accumulator of insects similar to the second trap. Powerful single LEDs with 365 and 395 nm of wavelength were used as efficient sources to attract insects. The LEDs in the traps were arranged in a circle, which evenly provided luminescence with an angle of 360°. In May 2018, the traps were tested on meadow grass. The collection of trapped insects was carried out every day. Insects that were trapped at regular time intervals were calculated by the number of individuals larger than 5 mm and the total weight. As a result, it was established that the conical trap equipped with an aspirator (AKL-2) was the most efficient. The efficiency of this trap is almost two times higher than that of the trap KL-2 and 20-30% higher than the trap KLP-1. The developed traps showed a high trapping ability and can be used in the production of specific agricultural crops to identify insects inhabiting them.